Co-occurrence of follicular thyroid carcinoma and Warthin’s tumor of the parotid gland: a rare case report - Adak, Arnab; Tripathy, Anannya; Guha, Rajdeep; Naskar, Sukanya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Synchronous thyroid and parotid tumors are rarely noted in literature. There are case reports with thyroid carcinoma with parotid metastasis. In this article we present a rare case of follicular thyroid carcinoma in a 62-year-old gentleman with a synchronous right sided Warthin’s tumor. Synchronous follicular thyroid carcinoma with a Warthin’s salivary tumor is a unique presentation and has not been reported in literature before to the best of our knowledge. The surgical management of such cases, particularly in a single sitting may prove challenging in terms of incision planning and execution and head and neck surgeons should be prepared for versatile surgical planning and postoperative care.